FRI0106 Influence of Optimization of Biological Therapies on Immunogenicity in a Cohort of Rheumatoid Arthritis with Low Disease Activity. (9th June 2015) - Paredes, B.; Plasencia, C.; Pascual-Salcedo, D.; Monjo, I.; Pieren, A.; Moral, E.; Tornero, C.; Bonilla, G.; Nuño, L.; Villalba, A.; Peiteado, D.; Ramiro, S.; et al.
Abstract : Background: Biological agents against tumor necrosis factor (Anti-TNF) have revolutionized the treatment of Rheumatoid Arthritis (RA). Recent studies assess the possibility of reducing the dose or increase the interval of administration of biologics (optimization strategy: OS) in patients with at least sustained low disease activity (LDA) without relevant clinical worsening. One of the questions raised is whether the use of OS could increase the incidence of anti-drug antibodies (ADA) appearance with the consequent loss of efficacy. Objectives: To evaluate the influence of the OS in a cohort of RA patients at least in LDA on the clinical activity (DAS28), incidence of flares, serum drug levels and ADA appearance. Methods: A retrospective observational study of a cohort of RA patients in LDA or remission (measured by DAS28<3.2 or<2.6, respectively) for at least 6 months. Of the 283 RA patients treated in our Unit with Infliximab (Ifx), Adalimumab (Ada) and Etanercept (Etn), 54 patients treated with the 1st Anti-TNF fulfilled the previous criteria to be included and were under an OS. DAS28, C reactive protein (CRP) values and drug and ADA levels were evaluated at baseline before OS (pre-visit) and in the last available visit during the first 2 years of follow-up (pos-visit). Flares were monitored between pre and pos-visits. Results: Of the 54 patients, 77.8% were women. Mean age was 60.2±12 years. The 79.6% (43) were antiCCP and FR positive. Regarding concomitant treatment 35 patients (64.8%) received methotrexate at baseline, 25 (46.3%) other DMARDs and 23 (42.6%) prednisone. Twenty-seven (50%) were treated with Ada, 16 (29.6%) with Etn and 11 (20.4%) with Ifx. No significant differences were observed in the control of DAS28 between the pre-visit and pos-visit in every Anti-TNF (Ada: 2, 13±0, 12 pre-visit vs 2, 42±0, 18 pos-visit, p=0, 064; Ifx: 2, 32±0, 11 pre-visit vs 2, 19±0, 18 pos-visit, p=0, 799; Etn: 2, 36±0, 12 pre-visit vs 2, 93±0, 20 pos-visit, p=0, 056). There was no statistically a significant increase in CRP levels between pre and post visits in any Anti-TNF (Ada: p=0, 629; Ifx: p=0, 799; Etn: p=0, 796). Nineteen (35.2%) developed flares during the follow-up (14 patients had one flare and 5 had 2 flares). All patients were negative for ADA at the pre-visit, 5 (9.25%) were positive at pos-visit associated with flares. Sixteen (29.6%) out of the 19 patients with flare required to shorten the interval or increase the dose to control DAS28. A statistically significant decrease was observed in drug levels between the pre-visit and post-visit in patients treated with Ada and Etn (Ada: 5127.88±1542.65 pre-visit vs 1200.29±276.52 pos-visit, p=0.003; Etn: 2794.46±367.07 pre-visit vs 1359.38±375.121 pos-visit, p=0.023). Conclusions: OS seems to be feasible in RA patients in LDA treated with Anti-TNF, reducing the amount of drug administered with low incidence of ADA and without impact on clinical and serological markers such as CRP. In most patients with flares, the clinical activity appears to be controlled by shortening the interval of administration without increasing the therapy discontinuation. Disclosure of Interest: B. Paredes Grant/research support from: This study has received unrestricted grants from Pfizer